Sidewall Aneurysm Geometry as a Predictor of Rupture Risk Due to Associated Abnormal Hemodynamics - Wan, Hailin; Ge, Liang; Huang, Lei; Jiang, Yeqing; Leng, Xiaochang; Feng, Xiaoyuan; Xiang, Jianping; Zhang, Xiaolong (Frontiers in Neurology, 2019)
Background: Hemodynamics play an important role in intracranial aneurysm (IA) initiation, growth, and rupture. Yet there remains no definitive quantitative analysis between abnormal hemodynamics and geometrical risk of IA development. Objective: The present study aims to investigate whether abnormal hemodynamics in IA sacs can be predicted by surrogate geometric markers. Methods: Computational fluid dynamics (CFD) simulations were performed on paraclinoid aneurysms derived from digital subtraction angiography (DSA) of 104 IAs in 104 patients. Four basic IA geometric parameters including maximum height, perpendicular height, maximum width, and neck diameter were measured. Abnormal hemodynamics were defined and quantified as the surface area exposed to low wall shear stress (WSS) and high oscillatory shear index (OSI) using objectively-defined thresholds. Relationships between abnormal hemodynamics and specific geometric parameters were analyzed via multiple linear regression. Results: Adjusting for age, sex, and other clinical characteristics, multiple linear regression revealed a significant relationship (p < 0.001) between abnormal hemodynamics and both maximum width (β ≈ 1.2) and neck diameter (β ≈ −0.4), but not maximum height or perpendicular height. These findings were shown to be independent of the choice of abnormal hemodynamic indicators and threshold levels. Conclusions: Maximum width and neck diameter of IA sacs are robust surrogates of exposure to abnormal hemodynamics. Risk of rupture may be increased with wider aneurysms with narrower necks for paraclinoid aneurysms.